2002
DOI: 10.1086/343768
|View full text |Cite
|
Sign up to set email alerts
|

The Central Nervous System as a Reservoir for Simian Immunodeficiency Virus (SIV): Steady‐State Levels of SIV DNA in Brain from Acute through Asymptomatic Infection

Abstract: Latent reservoirs of human immunodeficiency virus (HIV) present significant challenges for eradicating HIV from infected persons, particularly reservoirs in the brain established during acute infection. A simian immunodeficiency virus (SIV)/macaque model of HIV dementia was used to show that viral DNA levels in the brain remained at constant levels from acute through asymptomatic infection, despite significant down-regulation of viral RNA in the brain after the acute phase of infection. Viral replication in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
156
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(173 citation statements)
references
References 30 publications
14
156
1
Order By: Relevance
“…We have previously demonstrated that acute SIV replication is suppressed in the brain without the decrease in viral DNA levels, supporting the conclusion that transcriptional suppression occurs in the brain (3,4). The innate immune response to virus infection, particularly IFN␤ and the induction of LIP mediated by CUGBP1, is crucial for suppression of SIV transcription (4,47), thereby providing a mechanism for HIV/SIV latency in macrophages in the central nervous system.…”
supporting
confidence: 70%
See 4 more Smart Citations
“…We have previously demonstrated that acute SIV replication is suppressed in the brain without the decrease in viral DNA levels, supporting the conclusion that transcriptional suppression occurs in the brain (3,4). The innate immune response to virus infection, particularly IFN␤ and the induction of LIP mediated by CUGBP1, is crucial for suppression of SIV transcription (4,47), thereby providing a mechanism for HIV/SIV latency in macrophages in the central nervous system.…”
supporting
confidence: 70%
“…Once Tat is expressed, it binds to the TAR element, assisted by C/EBP␤ bound to the DS1 site and thus contributes, in part, to the surge of SIV RNA production and virus replication during acute infection (peaking at 10 days p.i.) in the brain (3,69). Virus replication in macrophages in the brain triggers the innate immune responses and production of IFN␤ (8,69), which activates CUGBP-1 required for IFN␤-induced translation of the dominant-negative LIP isoform (47).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations